Co-creation in English teaching: Enhancing student engagement and learning in an English language education program - Sahyoni, Sahyoni; Damanik, Lia Agustina; Oktarina, Hanifah (Journal of Language and Pragmatics Studies, 2025)
Innovative teaching approaches that foster active learning are increasingly recognized as essential in modern education. One such approach is co-creation, which emphasizes student engagement, collaboration, and shared responsibility in the learning process. This study aims to explore the implementation of co-creation in teaching Basic Grammar, Basic Writing, and Translation and analyse its impact on student learning outcomes. A qualitative research methodology was employed, focusing on students enrolled in the English Language Education Program. Data collection methods included focus group discussions, classroom observations, and interviews to gain insights into students’ experiences with co-creation-based instruction. The study was conducted at a higher education institution specializing in English language education. The findings reveal that various co-creation techniques—such as peer feedback, collaborative writing projects, grammar exercises, and interactive translation tasks—positively influenced student engagement, autonomous learning, and critical thinking. Students demonstrated a greater sense of responsibility in their learning, enhanced communication skills, and improved comprehension of language concepts. Additionally, co-creation facilitated a more interactive classroom environment where students actively contributed to the learning process rather than being passive recipients of knowledge. Overall, the study concludes that co-creation is an effective pedagogical strategy that enhances learning experiences in English language instruction. Its implementation fosters collaboration, motivation, and deeper understanding of grammar, writing, and translation. However, further research is recommended to examine quantitative impacts on student achievement, assess its applicability in broader educational settings, and explore potential challenges in implementation. Future studies may also investigate ways to optimize co-creation methods for different learning styles and subject areas.